Political Cartelization and the Empty Ballot Box Phenomenon in Regional Elections - Hadi Kusuma, Achmad Surya; Akhtar, Imranullah (Jurnal Mengkaji Indonesia, 2024)
Abstract: The phenomenon of "empty box" ballots in Indonesia's regional head elections (Pilkada) reflects public dissatisfaction with single candidates endorsed by political party coalitions. This highlights challenges within the local democratic system, which may hinder political participation and contribute to social instability. Purpose: This research aims to understand how the phenomenon of "empty box" ballots reflects the practice of political cartelization in Indonesia, as well as to explore the factors contributing to the emergence of single candidates and large coalitions in elections. Design/Methodology/Approach: The methodology employed in this research includes a qualitative analysis of national and local political dynamics, as well as an observation of voter behavior in the context of regional elections (Pilkada). The study also examines the implications of the "empty box" phenomenon for democratization and political representation at the regional level. Findings: The research findings indicate that the "empty box" phenomenon is not merely a matter of failed elections but also reflects a crisis of public trust in political institutions. Deep dissatisfaction with the available candidates has the potential to trigger radicalization and protest movements. Furthermore, the dominance of major political parties in candidate nomination disregards local aspirations, creating conditions where the nominated candidates fail to reflect the diversity of the community. Originality/value: This research offers new insights into the relationship between the "empty box" phenomenon and political cartelization practices in Indonesia, emphasizing the need for electoral system reforms to create a more inclusive space for public participation. By enhancing political awareness and strengthening smaller political parties, it is hoped that public dissatisfaction can be reduced, and the legitimacy of the political system can be improved.